Voltammetric determination of leucovorin in pharmaceutical preparations using a boron-doped diamond electrode - Šelešovská, Renáta; Kränková, Barbora; Štěpánková, Michaela; Kelíšková, Pavlína; Janíková, Lenka; Chýlková, Jaromíra; Navrátil, Tomáš (My University, 2018)
Method for voltammetric determination of leucovorin, a drug frequently applied to decrease some unfavorable effects of anticancer drugs such as methotrexate or to increase the therapeutic effect of 5-fluorouracil, has been developed employing a bare boron-doped diamond electrode. It is the first method for leucovorin determination based on its electrochemical oxidation. Although at least three anodic and three cathodic voltammetric peaks could be recorded under the used conditions, only the anodic response situated at about + 900 mV (vs. saturated Ag|AgCl electrode) was suitable, namely due to its shape and position, for analytical purposes. Using differential pulse voltammetry with optimized parameters and supporting electrolyte of pH 3.0, the linear dynamic range of leucovorin determination was recorded from 0.15 to 25 mu mol dm(-3). Under such conditions, low limit of quantification of 0.050 mu mol dm(-3) and limit of detection of 0.015 mu mol dm(-3) as well was reached. Relative standard deviation calculated from 11 repeated measurements amounted to 0.7% and calculated from five repeated determinations amounting less than 3.0%. Applicability of the developed method was verified by repeated analysis of the pharmaceutical preparation with excellent results (recovery 98.7-102.8%, relative standard deviation 1.81%).
Voltametrické stanovení leukovorinu ve farmaceutických vzorcích s využitím borem dopované diamantové elektrody
Keywords: Boron-doped diamond electrode; Determination; Leucovorin; Pharmaceutical samples; Voltammetry; Borem dopovaná diamantová elektroda; Stanovení; Leukovorin; Farmaceutické vzorky; Voltametrie